Emotional constraint, father-son relationships, and men's wellbeing - Cleary, Anne (Frontiers in Sociology, 2022)
Male rates of suicide exceed female rates and research findings indicate an association between particular practices of masculinity, specifically emotional constraint, and male suicide. This paper examines gender and family influences on men's wellbeing, based on in-depth interviews with a sample of fifty-two men, aged 18–30 years, who made a clinically serious or near-fatal suicide attempt and were recruited following presentation to hospital. Themes derived from the analysis included learning about masculinity which relates to the gender culture within the home, the regulation and enforcement of behavior by peers and father-son relationships. Results demonstrated that the men were generally from families where hegemonic ideals of masculinity, emphasizing strength and emotional stoicism, were practiced. This gender environment, which was reinforced in the neighborhood, restricted behavior and the expression of feeling, shaped communication between fathers and sons and affected the father's ability to emotionally engage with his son. Fathers were significant figures in these men's lives and were role models for demonstrating masculinity practices but there was an absence of positive, nurturing, relationships between fathers and sons and this influenced the son's gender learning and his wellbeing. Fathers who were emotionally distant, and particularly those who were abusive, gave rise to feelings of rejection, sadness and anger in their sons but problematic father-son relationships were not addressed nor ill-treatment in childhood disclosed due to gender-related constraints on expression. Restrictions on expression and prohibitions on revealing weakness denied the men a space to explore as well as manage the issues of their lives and prevented them from revealing distress. They coped by sublimating problems and disguising vulnerability and by seeking emotional comfort within intimate partnerships but these men were susceptible to situations which threatened their psychological security. Overall, the study demonstrated challenges for males raised in settings of hegemonic masculinity and the importance of nurturing father-son relationships for male wellbeing. The results imply the need for a focus on the benefits of positive fathering and the inclusion of more nuanced messaging relating to men's emotions in Public Health messaging.